Do ancient wheats contain less gluten than modern bread wheat, in favour of better health?. Issue 2 (13th May 2022) - Brouns, Fred; Geisslitz, Sabrina; Guzman, Carlos; Ikeda, Tatsuya M.; Arzani, Ahmad; Latella, Giovanni; Simsek, Senay; Colomba, Mariastella; Gregorini, Armando; Zevallos, Victor; Lullien‐Pellerin, Valerie; Jonkers, Daisy; et al.
Abstract: Popular media messaging has led to increased public perception that gluten‐containing foods are bad for health. In parallel, 'ancient grains' have been promoted with claims that they contain less gluten. There appears to be no clear definition of 'ancient grains' but the term usually includes einkorn, emmer, spelt and Khorasan wheat. Gluten is present in all wheat grains and all can induce coeliac disease (CD) in genetically susceptible individuals. Analyses of 'ancient' and 'modern' wheats show that the protein content of modern bread wheat ( Triticum aestivum ) has decreased over time while the starch content increased. In addition, it was shown that, compared to bread wheat, ancient wheats contain more protein and gluten and greater contents of many CD‐active epitopes. Consequently, no single wheat type can be recommended as better for reducing the risks of or mitigating the severity of CD. An estimated 10% of the population of Western countries suffers from gastrointestinal symptoms that lack a clear organic cause and is often referred to as irritable bowel syndrome (IBS). Many of these patients consider themselves gluten sensitive, but in most cases this is not confirmed when tested in a medical setting. Instead, it may be caused by gas formation due to fermentation of fructans present in wheat or, in some patients, effects of non‐gluten proteins. A significant overlap of symptoms with those of CD, IBS and inflammatory bowel disease makes a medical diagnosis a priority. This critical narrative review examines the suggestion that 'ancient' wheat types are preferred for health and better tolerance.